A study of socio-cultural elements in common proverbs in Khorasan Razavi with emphasis on Kashmar city - zendeh del, Hamid (2021)
One of the manifestations of culture and civilization and even literature of any country is the proverbs, rulings and short and rich words that arise from the greats of science and literature or from the common people and in our vast and ancient language there are thousands of proverbs and words Which has taste, thought and kindness and good interpretation in saying the meaning. The people of a society, when they find their experiences and reserves and those of the past as accepted and certain facts, express them in short sentences, in the form of poetry or prose, so that when they use them, the audience Immerse yourself in deep thought and leave a lasting impression on him. In fact, proverbs are the essence of a nation's collective wisdom that has been polished over time and passed down to us heart to heart. In our country, due to its ancient history, there are many proverbs. Although in different Iranian ethnic groups these proverbs have differences in language and dialect, but many of them are common in terms of meaning or concept. This article tries to examine the socio-cultural elements of the proverbs common in Kashmar city, its roots, dialect and their uses.